Combined effects of exercise and different levels of acute hypoxic severity: A randomized crossover study on glucose regulation in adults with overweight - Tee, Chris Chow Li; Parr, Evelyn B.; Cooke, Matthew B.; Chong, Mee Chee; Rahmat, Nurhamizah; Md Razali, Mohd Rizal; Yeo, Wee Kian; Camera, Donny M. (Frontiers in Physiology, 2023)
Purpose: The aim of this study was to investigate the influence of manipulating hypoxic severity with low-intensity exercise on glucose regulation in healthy overweight adults. Methods: In a randomized crossover design, 14 males with overweight (age: 27 ± 5 years; body mass index (BMI) 27.1 ± 1.8 kg⋅m2) completed three exercise trials involving 60 min aerobic exercise cycling at 90% lactate threshold in normoxia (NM, FiO2 = 20.9%), moderate hypoxia (MH, FiO2 = 16.5%) and high hypoxia (HH, FiO2 = 14.8%). A post-exercise oral glucose tolerance test (OGTT) was performed. Venous blood samples were analyzed for incremental area under the curve (iAUC), plasma glucose and insulin, as well as exerkine concentrations (plasma apelin and fibroblast growth factor 21 [FGF-21]) pre- and post-exercise. A twenty-four-hour continuous glucose monitoring (CGM) was used to determine interstitial glucose concentrations. Heart rate, oxygen saturation (SpO2) and perceptual measures were recorded during exercise. Results: Post-exercise OGTT iAUC for plasma glucose and insulin concentrations were lower in MH vs control (p = 0.02). Post-exercise interstitial glucose iAUC, plasma apelin and FGF-21 were not different between conditions. Heart rate was higher in HH vs NM and MH, and MH vs NM (p < 0.001), while SpO2 was lower in HH vs NM and MH, and MH vs NM (p < 0.001). Overall perceived discomfort and leg discomfort were higher in HH vs NM and MH (p < 0.05), while perceived breathing difficulty was higher in HH vs NM only (p = 0.003). Conclusion: Compared to higher hypoxic conditions, performing acute aerobic-based exercise under moderate hypoxia provided a more effective stimulus for improving post-exercise glucose regulation while concomitantly preventing excessive physiological and perceptual stress in healthy overweight adults